HUBUNGAN SIKAP KERJA DENGAN MUSCULOSKELETAL DISORDERS PADA PENJAHIT DI PUSAT INDUSTRI KECIL MENTENG MEDAN 2015 - agnes putri; kalsum *; makmur sinaga (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTMusculoskeletal Disorders (MSDs) is a medical disorder of muscle tissue and bonestructure. This research was aimed to find out the correlation of working posture withMusculoskeletal Disorders (MSDs) the tailors at Pusat Industri Kecil Menteng Medan in2015.This research is an observational analytical with Cross Sectional design. Thesample of 31 research tailors obtained by used was Total Sampling technique. The datacollection was done using by RULA Assessment Worksheet and Nordic Body Map (NBM).The data analysis used Exact Fisher test.Based on the working posture with RULA assessment method , the unnatural posture wasfound in the body of the neck is ≥ 200 by 100% of tailors and the trunk is ≥ 200 by 64.5% oftailors with at a high level 67.7% and a very high level 32.3% . The tailors (100%) areMSDs with complaints in the neck, trunk, right shoulder and right calf with a mediumlevel of 71.0% and a high level of 29.0% .Results of bivariate analysis , known correlation the working posture withMusculoskeletal Disorders with P value=0.015, which means there is a significantcorrelation between working posture with Musculoskeletal Disorders the tailors at PusatIndustri Kecil Menteng Medan in 2015.Suggested that tailors shall perform stretching while working and doing back exercisesbefore going to bed at night .